Fetal ST baseline T/QRS rise in normal CTG does not predict neonatal acidemia. (18th August 2021) - Vettore, Michela; Straface, Gianluca; Tortora, Domenico; Parotto, Matteo; Greco, Pantaleo; Ugwumadu, Austin; Zanardo, Vincenzo
Abstract: Purpose: Analysis of the ST segment of the fetal electrocardiogram (ECG) waveform is a relatively new adjunct to support the cardiotocograph in assessing the risk of significant intrapartum fetal acidosis. The use of ST analysis (STAN) combined with cardiotocography (CTG) was reported to significantly lower the incidence of metabolic acidosis. We aimed to assess the role of "baseline T/QRS rise" associated with a normal CTG on the risk of neonatal acidemia. Study design: This is a prospective cohort study performed at the Division of Perinatal Medicine of Policlinico Abano Terme, Italy. Women in labor with a singleton fetus in cephalic position beyond 36 weeks of gestation were monitored with STAN and CTG. Patients and methods: The relationship between "baseline T/QRS rise" and neonatal cord arterial acidemia and hypoxic distress were assessed using a linear mixed-model analysis. Magnitude of "baseline T/QRS rise", neonatal cord blood acidemia, electrolytes, lactacidemia, and glycemia levels were measured. Results: "Baseline T/QRS rise" was not associated with neonatal acidemia in the presence of normal CTG, regardless of the magnitude of the T/QRS rise. However, in a linear mixed-model analysis, cord blood sodium levels were negatively ( p  = .033) associated with T/QRS ratio magnitude. Conclusions: In the presence of a normal CTG, "baseline T/QRS rise" does not predict neonatal acidemia or biochemical derangement. Greater knowledge of fetal ECG parameters including "baseline T/QRS rise" and their associations with normal, intermediary, and abnormal CTG tracing, is required in assessing the performance of the STAN.